Review to the roots of shamluâs poetic imagery - یعقوب نوروزی (مطالعات زبانی و بلاغی)
Imagery is one the fundamental elements in poetry. Innovation in imagery and emphasis on the individual points of view have an important effect on the rhetorical attribute of poem. Because of this we debate about this traits of shamlu’s poem. Individualism, objectivity and innovation are three traits of shamlu’s imagery which we discuss about it in this article. Then we mention examples of shamlu’s poems about roots of imagery.  One of the important roots of shamlu poetic imagery is the modern life. In shamlu’s poem, life of a modern cities artistically is reflected and a also poet with a perfect masterpiece invents contemporary images from this type of life can be seen. Beside this, shamlu attains in his poetic imagery to the myths. Mythology of shamlu contains more elements of Greek mythology. shamlu with assistance of myth, affair  as well as transition of his idea and point of view. Iranian myth is the other mythological root of shamlu’s imagery.in this section Ferdowses Shahname has an effect and shamlu with a usage of Iranian ancient heroes efforts influnce the addressees.